Removing heavy metals and improving the dewaterability of sewage sludge with the bioleaching process by Thiobacillus Ferrooxidans bacteria - Reza Shokoohi; Roya Najafi-Vosough; Amir Shabanloo; Zahra Torkshavand; Mohammad Molla Mahmoudi; Mohammad attar abasi (Applied Water Science)
Abstract Bioleaching technology is being developed as a cost-beneficial and environmentally friendly strategy for the removal of metal ions from sewage sludge. Therefore, this study aims to evaluate the feasibility of bioleaching process for the removal of heavy metals (Pb, Al, Zn, and Cu) from sewage sludge using indigenous iron-oxidizing microorganisms. For this purpose, 10 mL of a sludge-enriched inoculum of iron-oxidizing bacteria with 2 g FeSO4.7H2O was added to a 250-mL Erlenmeyer flask containing 100 mL of the sludge mixture from the secondary and primary sedimentation unit (34.78 g L−1 solids). The samples were stirred in a shaking incubator at 28 °C and 120 rpm for 15 days and analyzed for pH, oxidation–reduction potential (ORP), Fe3+ and heavy metal concentration. In parallel, control samples were performed with 100 mL of sludge sample without the addition of the sludge-enriched inoculum and energy source. It was observed that the concentration of heavy metals decreased continuously over the period of 15 days and the removal efficiency reached 62.7%, 80.7%, 43%, and 75.5% for Al, Cu, Pb, and Zn, respectively. On the other hand, the changes in selective heavy metal removal in the control experiments are very negligible. The results also showed that the specific filtration resistance (SRF) of the sludge decreased by 66.87%. In addition, the results of the SEM, EDX − mapping and XRD analyses before and after the bioleaching experiments confirm the activities of the microorganisms. The results clearly showed that the bioleaching process is an effective approach for removing heavy metals from sewage sludge as well as improving sludge dewatering and reducing the subsequent costs for the dewatered sludge disposal.